The Impact of Socioeconomic Factors on The Level Of Achievements In Grade 5 Scholarship Examination – A Study In Kantharmadam Area - Srikanthan, S.; Elankumaran, C. (University of Jaffna, 2009)
This study focuses on the description of the influence of socioeconomic factors on the level of achievements in grade 5 scholarship examination in Kantharmadam area of Nallur Divisional Secretariat Division during the period from 2003 to 2007. The socio – economic factors such as housing environment, economic status of the family, school environment, and characteristics of the student, social environment, and political situation in the county were subjected to investigation in Kantharmadam village of about 1950 inhabitant families. The specific objective of this study is to explore the influence of the above socioeconomic factors on the level of achievement. The method adopted in this study is a cross – sectional research design and a simple random sample of 50 families selected from the sub-population of Kantharmadam which has the children who have appeared for the scholarship examination during the year 2003 to 2007. The four Grama Officer divisions including in Kantharmadam area were considered to draw the sample families proportionately. An interviewer administered questionnaire was employed to collect primary data on the above said socioeconomic characteristics. Secondary information about the achievements in scholarship exams were also collected from the three primary schools functioning in Kantharmadam. Quantitative analysis was employed on the summary information compiled in frequency tables. The investigation on the level of income of parents shows positive impact on the level of achievements. This result was found to be coincidental with housing environment. Some of the students show low level achievements as they are unable to get admission in the leading schools due to family economic drawbacks. School environment make positive impacts due to various facilities including extra classes. Characteristics of the student and social environment do not show much influence, but the qualitative inquiry shows that the political situation gives negative impacts on the level of achievements. It is therefore suggested that two separate examinations be conducted one for awarding financial benefits to the poor students and other for high school admissions to all the students. Quota system be adopted for the benefit of the poor students. The facilities for preparing and appearing for the examinations from the less- popular schools be addressed.
Keywords: level of achievements; cross – sectional Design; socioeconomic factors